THE EFFECT OF PROJECT BASED LEARNING USING CANVA ON STUDENT’S ABILITY TO WRITE HEALTH PROMOTION TEXT - Harahap, Ardi Ficri; Fahmi, Khairul (Getsempena English Education Journal, 2024)
Proficiency in writing health promotion texts is crucial for nursing students in English language learning. However, limited writing proficiency remains a significant barrier. This study aims to investigate the impact of the Project-Based Learning (PjBL) approach, using Canva application, on students’ ability to write health promotion text. A quasi-experimental with non-randomized pre-test post-test design was utilized, involving 76 nursing students from STIKes Medika Seramoe Barat as the population and sample. The students were divided into two groups; an experimental group taught using project based learning with Canva and a control group receiving traditional teaching approach. Data were collected through writing test, in form of pre-test and post-test evaluations, and analyzed using the Mann-Whitney test. The findings reveal that project based learning using Canva application significantly improved students’ writing skills (Sig. (2-tailed) .001 < 0.05). These results suggest that incorporating Project based learning with digital tools like Canva is an effective pedagogical strategy for fostering nursing students' academic writing competencies.